Design Formulae of Wave Transmission due to Oblique Waves at Low Crested Structures - Siladharma, I Gusti Bagus (Jurnal Teknik Sipil, 2011)
Abstract. Low crested structures, including submerged breakwaters, may be provided to protect the beach from wave attack. These structures can be built parallel to the shoreline and the crest is set up at or below water levels. It function is to protect the beach from wave action by reducing or by acting as a barrier to the waves. Wave transmission on structures has been subject for flume tests by many researchers and come up with several 2D wave transmission formulas. Oblique wave attack rarely involve on the formula since only a few tests conducted on 3D model. Using 3D test data conducted by Seabrook (1997), wave-structure interaction relation in 3D effect was modeled and transmission formula for low crested structures was developed. The interaction of wave-structure in the 3D modeling is more complex. The complex, three dimensional wave-structure interactions include diffraction of the wave. Results show the relative crest height, relative wave height and crestÂ  width are the most important parameters. The model was developed by statistical analysis method, includes parameters that are considered to be representing physical processes such as water depth fluctuation, hence is related to wave breaking, wave overtopping, dissipation by surface friction, and transmission through the breakwater. Abstrak. Pemecah gelombang ambang rendah, termasuk pemecah gelombang tenggelam, dapat dipergunakan sebagai pelindung pantai dari serangan gelombang. Stuktur dengan ambang lebar ini dibangun sejajar pantai dengan puncak berada pada muka air atau sedikit di bawahnya. Fungsi utama dari bangunan ini adalah melindungi pantai dari gelombang dengan cara mereduksi energi gelombang datang atau sebagai penghalang gelombang. Bangunan ini berfungsi dengan baik dengan meredam sebagian energi gelombang. Transmisi gelombang pada pemecah gelombang ambang rendah tumpukan batu sudah banyak diteliti dan menghasilkan beberapa formula yang dihasilkan dari tes 2 dimensi. Gelombang yang datang menyudut terhadap struktur tidak diperhitungkan karena sangat terbatasnya penelitian transmisi gelombang dalam kondisi 3D. Menggunakan data 3D dari Seabrook (1997), analisis dilakukan untuk interaksi gelombang-struktur dan formula empiris transmisi gelombang diturunkan. Interaksi gelombang-struktur dalam model 3D lebih komleks dari model 2D. Kekompleksan dalam model 3D termasuk adanya proses difraksi pada ujung-ujung pemecah gelombang, Hasil penelitian menunjukkan bahwa tinggi puncak relatif, tinggi gelombang relatif, dan lebar puncak merupakan parameter yang sangat berpengaruh terhadap proses transmisi Rumus empiris diturunkan berdasarkan analisis statistik. Rumus transmisi gelombang memasukkan parameter-parameter yang merepresentasikan proses-proses fisik seperti fluktuasi muka air, yang berkorelasi dengan gelombang pecah, overtopping gelombang, disipasi akibat gesekan permukaan, dan transmisi gelombang melalui bangunan.